Membangun Nilai Karakter Religius Siswa di Kelas 5 SD IT Rabbani Bone - Jusni Jusni; Ilham Samudra Sanur; Bustan Bustan (STKIP AL HIKMAH SURABAYA, 2025)
The urgency of instilling religious character has become increasingly critical due to the moral decline observed among Indonesia's younger generation, including disobedience to religious teachings, dishonesty, and a lack of respect for others, including teachers. Religious character is expected to provide a solution by shaping students to possess strong and virtuous morals. This study aims to describe the implementation of religious character values at SD IT Rabbani in Bone Regency. Using a qualitative approach with a descriptive method. Data collection techniques involved observation and interviews, validated through triangulation. The results of the study show that SD IT Rabbani successfully integrates religious values through various activities such as tahfidz Al-Qur'an, daily worship habits, and literacy programs. The tahfidz Al-Qur'an program helps students love and memorize the Qur'an using systematic and enjoyable methods. Daily worship habits foster positive habits, discipline, and spiritual calm among students.